THE INFLUENCE OF ORGANIZATIONAL CLIMATE AND SELF EFFICACY ON INNOVATIVE WORK BEHAVIOR STUDY AT PT TRIKARYA CEMERLANG AREA RDTX GROUP - Rosdiana Syafitri; Tedi Lukman; Agung Surya Dwianto (LP2M Universitas Bina Bangsa, 2024)
This study aims to deeply understand the influence of organizational climate and self-efficacy on innovative work behavior in employees of PT Trikarya Cemerlang Area RDTX Group. Using a qualitative approach with a case study design, this research involved in-depth interviews, participant observation, and document analysis. The results showed that an organizational climate that supports innovation, such as tolerance for risk and rewards for new ideas, has a positive impact on employees' innovative work behavior. In addition, self-efficacy was also proven to be an important factor that encourages employees to be more proactive in generating new ideas and taking risks. The interaction between organizational climate and self-efficacy creates a positive cycle that reinforces innovative behavior. The findings of this study have important implications for companies in designing strategies to enhance innovation